2021
DOI: 10.2478/emj-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on logistics firms and their resilience: case studies in Thailand

Abstract: The novel Coronavirus (COVID-19) is an infectious disease that is currently causing challenges and opportunities in all sectors worldwide. The logistic industry plays an enormous role in keeping the countries functional, and it accounts for 13.4 % of the total GDP in Thailand. This article aims to identify and justify critical success factors for the Logistic Industries experiencing success and failure during the pandemic. The research was conducted using semi-structured interviews with top managers of three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Finally, outcomes of this study show that the L&T field is somehow unique compared to the remaining sectors. Results from the current literature show that Covid-19 impacted on L&T, with some companies experiencing a negative impact and others being relatively less affected by the pandemic ( Ketudat and Jeenanunta, 2021 ; Perkumiene et al, 2021 ). However, the analysis of different time horizons and the multi-sectorial perspective allows this study to provide additional findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, outcomes of this study show that the L&T field is somehow unique compared to the remaining sectors. Results from the current literature show that Covid-19 impacted on L&T, with some companies experiencing a negative impact and others being relatively less affected by the pandemic ( Ketudat and Jeenanunta, 2021 ; Perkumiene et al, 2021 ). However, the analysis of different time horizons and the multi-sectorial perspective allows this study to provide additional findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, although authors have suggested that the effects of Covid-19 have been different across the industrial sectors ( Xu et al, 2020 ; De Vet et al, 2021 ), the available studies have provided evidence on some sectors only. While L&T, in its various segments, has been somehow discussed (e.g., Perkumiene et al 2022; Hohenstein, 2022 ; Ketudat and Jeenanunta, 2021 ), other sectors (e.g., MACH or MEM) have been almost neglected in literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations